News Feed Advertising and Positive Attitude: An Interpretation Model Based on Information Processing - Du, Qinglong; Yang, Yanxia; Liu, Ying; He, Qiqi (Frontiers in Psychology, 2021)
This study mainly examines the different effects and mechanisms of news feed advertising (vs. traditional display advertising) on advertising attitude and brand attitude by using an observational experiment that categorized participants based on their past experiences. By analyzing the video advertising of the “Li Ning” brand, three conclusions were drawn. First, compared with traditional display advertising, news feed advertising led to more positive advertising attitude and brand attitude. Second, generation and transmission mechanism of attitudes were applicable to the interpretation rules of the classical information processing process model, which showed that the information processing process of the news feed advertising and the traditional display advertising were consistent. Third, consumer’s brand experience did not affect the direct effects of “attention” on “memory”, but affected the mediate role of “interpretation”, which showed that news feed advertising may have a stronger “drainage” effect when promoting new products and developing new markets. However, if the consumer’s experience is not enhanced, the brand attitude triggered by news feed advertising will still not be stable. These findings are conducive to further understanding the effect of news feed advertising on advertising attitude and brand attitude.